2021
DOI: 10.2302/kjm.2021-0005-oa
|View full text |Cite
|
Sign up to set email alerts
|

Identification of B.1.346 Lineage of SARS-CoV-2 in Japan: Genomic Evidence of Re-entry of Clade 20C

Abstract: SARS-CoV-2 whole-genome sequencing of samples from COVID-19 patients is useful for informing infection control. Datasets of these genomes assembled from multiple hospitals can give critical clues to regional or national trends in infection. Herein, we report a lineage summary based on data collected from hospitals located in the Tokyo metropolitan area. We performed SARS-CoV-2 whole-genome sequencing of specimens from 198 patients with COVID-19 at 13 collaborating hospitals located in the Kanto region. Phyloge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A number of SARS-CoV-2 strains emerged in Southern California in late 2020, spanning the November 2020-March 2021 COVID-19 surge, driven largely by mutations in the spike protein 26 and described by Zhang et al 27 . The dominant clades were: 20 A (lineage B.1.234 26 ), 20B (lineage B.1.1.220/B.1.1.222 26 ), 20 C (lineage B.1.346 28 ), and 20 G (lineage B.1.2 26 ). Clade CAL.20 C, later assigned the lineage B.1.427/B.1.429 29 , also was gaining prominence over this period 27 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of SARS-CoV-2 strains emerged in Southern California in late 2020, spanning the November 2020-March 2021 COVID-19 surge, driven largely by mutations in the spike protein 26 and described by Zhang et al 27 . The dominant clades were: 20 A (lineage B.1.234 26 ), 20B (lineage B.1.1.220/B.1.1.222 26 ), 20 C (lineage B.1.346 28 ), and 20 G (lineage B.1.2 26 ). Clade CAL.20 C, later assigned the lineage B.1.427/B.1.429 29 , also was gaining prominence over this period 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work and other work on the genome sequence of SARS-CoV-2 obtained from Japan showed that most, if not all, of the lineages observed between June and November 2020 were the B.1.1.284 or B.1.1.214 lineages, both of which have been observed almost exclusively in Japan [ 11 , 16 ]. Further analysis of the metadata of B.1.1.284 and B.1.214 from Hokkaido alone and all Japan showed that the B.1.1.284 lineage was the most prevalent lineage during the late summer of 2020 and the B.1.1.214 lineage became more prevalent after October 2020 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Phylodynamic analysis [ 9 ], including subsampling, alignment, phylogenetic inference, temporal dating of ancestral nodes, and discrete trait geographic reconstruction, as well as inference of the most likely transmission events, was performed using the Nextstrain pipeline suite [ 10 ], as previously described [ 11 ]. Briefly, we aligned sequences, subsampled sequences (see below), added sequences from the rest of the world for phylogenetic context based on genomic proximity, reconstructed the phylogeny using IQ-Tree version 2.1.2 [ 12 ].…”
Section: Methodsmentioning
confidence: 99%